Estratégias de ensino de Língua Inglesa e afetividade na EJA: olhares múltiplos - Satyro, Diego (2018)
This study is about the strategies for English (as a foreign language) teaching and the expressions of emotions and feelings in the field of Adult and Youth Education (equivalent to EJA, in Brazil). The research purposes are to identify and to interpret the strategies for English teaching used by the participants and to explain the role of emotions and feelings in this process. The literature review is organized into studies on the history of Adult and Youth Education in Brazil, on the profile of students who enroll in these courses, on the status of English as a subject in Brazilian public schools, on the post-method condition, on the interdependence between emotion and cognition, on the Spinozistic monism, on the Freirean approach, on the Henri Wallon’s developmental psychology and on teacher education to and in the field of Adult and Youth Education. The setting is two state junior high schools with adult and youth classes in the evening. The schools are near slums of São Bernardo do Campo, São Paulo. This study includes three teachers, besides the researcher. The research method is the qualitative interpretative research, particularly the collective case study. In 2016, to gather the data, I designed pre and post-questionnaires, carried out individual interviews, observed and recorded classes, obtained the teachers’ lesson plans, had informal conversations with them, and communicated through text messages. The data analysis show that the participants’ previous experiences, the language-teaching supplementary materials, the school approach to curriculum design and the pre-service and in-service teacher education play crucial roles in the choice of strategies for teaching English. Furthermore, teachers who create emotional bonds with their students are more successful in engaging them in English language-learning tasks. However, the understanding of emotions and feelings as a substantial part of the teacher’s agency is not clear to every participant